FAKTOR – FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR KOPI INDONESIA KE JEPANG - Ayu Sitanini; Agus Sutanto; Irene Kartika Eka Wijayanti (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
The increase in coffee consumption in Japan is caused by several reasons, including changes in lifestyle in society due to westernization which introduced the habit of drinking coffee. Marketing that emphasizes instant coffee and roasted or ground coffee beans, a fast growing cafe or coffee shop. The product innovation process is increasingly developing so that Japanese people can enjoy coffee more easily. The research objective was to determine the factors that influence the volume of Indonesian coffee exports to Japan. The research method in this research uses quantitative methods. Type of data used is secondary data in the form of time series data from 1989 to 2018. The data sources were obtained from the directorate general of the United Nations and Commodities of Trade (UN Comtrade), World Bank. The analysis used multiple linear regression models through the ECM approach. The results showed that an increase in Japanese population, world tea prices and Indonesia Japan Economics Partnership (IJEPA) policies would increase the volume of Indonesian coffee exports to Japan. While Japanese coffee consumption, world coffee prices and inflation reduce the volume of Indonesian coffee exports to Japan. The increase in coffee production, Japanese GDP and the exchange rate did not increase or decrease the volume of coffee exports to Japan. Keywords: coffee, exports, consumption, error correction model